Report on WFEO general assembly & world congress on engineering and digital divide, 12-19 October 2003, Tunisia - Mohd. Rasid, Osman, Ir.; Megat Johari, Megat Mohd. Noor, Ir. Assoc. Prof.; Abang Abdullah, Abang Ali, Ir. Prof. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/